2015
DOI: 10.1080/03057240.2015.1048791
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of young students’ core virtues of e-character education: The Taiwanese teachers’ perspective

Abstract: The e-character education (e-CE) approach refers to systems of ethics education that pertain specifically to cyberspace. This exploratory study used a survey to collect 2495 teachers' responses regarding virtues important to e-CE. Furthermore, in order to identify the teaching concerns associated with these most important virtues, this study used two focus groups that involved interviews with 16 teachers and Internet experts, as well as a content analysis of 92 posts from 72 teachers in an online course regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…Based on the country, a total of six studies focused on Asian teachers' perception of values education implementation [13], [18], [22]- [25].…”
Section: Results and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the country, a total of six studies focused on Asian teachers' perception of values education implementation [13], [18], [22]- [25].…”
Section: Results and Findingsmentioning
confidence: 99%
“…Teachers did not plan to incorporate values into teaching lesson instead of teaching values by spontaneously. Chang and Chou (2015) studies found that teachers faced difficulty with explaining to their students about good virtue during the e-character education (CE) lesson [25]. On the contrary, Maphalala and Mpofu (2018) studies reveal that teachers used diverse strategies to teach values such as case studies, role-plays and discussion [32].…”
Section: A What Do Teachers' Recognize As Challenges To Implement Vamentioning
confidence: 99%
“…There are also a few other studies centering on this topic that do not use teacher mediation theory. Chang and Chou (2015) focused on what they call "e-character education" and investigated Taiwanese teachers' perspectives on core virtues in cyberspace that young people need to learn. Based primarily on a questionnaire and focus groups, they concluded that teachers thought that core virtues needed online were law abidance, respect, and self-discipline.…”
Section: Mediating Children's Digital Technology Usementioning
confidence: 99%
“…It is believed that all people through a process of learning that is directed and reasonable can form themselves have a stronger and stronger character. Based on the results of research conducted by Chih Ming Chang and Cien Chou from the Institute of Education, National Chiao Tung University, Taiwan shows that the virtue of character education that is considered important is respect, discipline, and social sharing [4].…”
Section: A Charactermentioning
confidence: 99%